2019
DOI: 10.1021/acs.jpcc.8b12085
|View full text |Cite
|
Sign up to set email alerts
|

Application of Static Disorder Approach to Friction Force Microscopy of Catalyst Nanoparticles to Estimate Corrugation Energy Amplitudes

Abstract: Friction force microscopy (FFM) of materials with well-defined crystalline surfaces is interpreted within the framework of the Prandtl–Tomlinson (PT) model. This model portrays the interaction with a surface through a deterministic periodic potential. While considering materials with polycrystalline or amorphous surfaces, the interpretation becomes more complex, since such surfaces may lack distinct lattice constant and/or corrugation energy amplitude. Here, we utilize an approach to describe the nanofriction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…The interaction potential between the tip apex and the sample is given as symmetric periodic function where U 0 F N is the amplitude of the corrugation potential at a given normal load F N , and a is the lattice periodicity. As previously mentioned, the applied normal load is related to the amplitude of the corrugation potential [35,36,41,57,64,65]. Following our previous work [57], we quantify this dependency by approximating a (single periodic) local minimum and its consecutive maximum in the interaction potential, which can be written in terms of a reduced bias field [14,66]:…”
Section: Ffm Numerical Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The interaction potential between the tip apex and the sample is given as symmetric periodic function where U 0 F N is the amplitude of the corrugation potential at a given normal load F N , and a is the lattice periodicity. As previously mentioned, the applied normal load is related to the amplitude of the corrugation potential [35,36,41,57,64,65]. Following our previous work [57], we quantify this dependency by approximating a (single periodic) local minimum and its consecutive maximum in the interaction potential, which can be written in terms of a reduced bias field [14,66]:…”
Section: Ffm Numerical Simulationsmentioning
confidence: 99%
“…During a scan, the tip bends and releases with respect to its position along the atomic-scale periodicity of the sample (for ordered surfaces), and produces a stick-slip pattern in the lateral force signal. Studies on nanoscale friction have shown that several properties influence this dynamics, such as contact area [4][5][6][7][8][9], sliding velocity [10][11][12][13][14][15][16], temperature [11,[17][18][19][20][21][22][23], anisotropy, symmetry and dimensionality [13,[24][25][26][27][28][29][30][31][32][33], and the applied normal load [4,5,23,26,[33][34][35][36][37][38][39][40][41][42][43].…”
Section: Introductionmentioning
confidence: 99%